Wnt signaling: implications in endoderm development and pancreas organogenesis. (December 2019) - Scheibner, Katharina; Bakhti, Mostafa; Bastidas-Ponce, Aimée; Lickert, Heiko
Abstract : The pancreas is derived from the foregut endoderm during embryonic development. After gastrulation and endoderm germ layer formation complex morphogenetic events coupled with cell differentiation programs pattern the gut tube and induce pancreas organogenesis. This results in formation of exocrine, ductal and hormone-producing endocrine cells. Among these, endocrine cells are responsible for blood glucose homeostasis and their malfunction leads to diabetes mellitus, which cannot be stopped or reversed by the current standard treatments. Thus, intense efforts to regenerate or replace the lost or dysfunctional insulin-producing β-cells are on the way. This depends on identifying the factors that coordinate pancreas organogenesis. Here, we highlight the contribution of canonical and non-canonical Wnt signaling branches in orchestrating endoderm formation, pancreatic morphogenesis as well as endocrine cell formation and function.